SUCCESS RATE OF PERCUTANEOUS CORONARY INTERVENTION FOR CHRONIC TOTAL OCCLUSION (Vietnam Journal of Community Medicine, 2022)
Background: Chronic Total Occlusion (CTO) is a significant challenge in percutaneous coronary intervention on account of the high likelihood of interventional failure. Due to lack of data regarding this procedure in Vietnam, we conducted this study to gather additional data on CTO intervention in diverse patient populations.Objectives: (Determine the success rate and the variables associated with procedural failure of percutaneous coronary intervention for chronic total occlusion lesions).Methods: We conducted a observational trial on patients undergoing percutaneous coronary intervention for chronic total occlusion lesions at University Medical Center Ho Chi Minh City, from April 2017 to June 2019.Results: The mean age of the study participants was 67.3±11.3, and 73.7% of them were male. Co-morbidities were hypertension (82.5%), old myocardial infarction (26.3%), prior percutaneous coronary intervention (26.3%), diabetes mellitus (29.9%), chronic kidney disease (9.8%). Acute coronary syndrome was diagnosed in 77.4% of patients. SYNTAX I average score was 21.7±7.2. The procedural success rate was 87.1%, and the characteristics associated with procedural failure were BMI > 25kg/m2, high J-CTO score, J-CTO score ≥ 3; ambiguous proximal cap, turtuos vessel, cacified vessel and retrograde CTO approach and without use of intravascular ultrasound.Conclusion: Our study found that the successful rate of percutaneous coronary intervention for chronic total occlusion lesion is high (87.1%) and variables associated with procedural failure are BMI >25 kg/m2; high J-CTO score, J-CTO score ≥ 3, tortuous and calcified vessel, blunt stump, retrograde CTO approach and without use of intravascular ultrasound.
Keywords: Chronic total occlusion, pertacuneous coronary intervention, antegrade, retrograde.